Meditrack: A Gui-Based Clinic Appointment and Patient Record Management System with MYSQL Storage and Excel Backup (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Manual management of clinic appointments and patient records can cause delays, misplaced files, duplicate entries, inaccurate information, and difficulty in retrieving patient data. To address these problems, this study developed MediTrack, a GUI-based Clinic Appointment and Patient Record Management System designed to help clinic staff manage patient information and appointment records in a faster, more organized, and more reliable manner. The system was developed using Python as the main programming language, Tkinter for the graphical user interface, MySQL for permanent database storage, and OpenPyXL for automatic Excel backup. MediTrack includes important features such as secure login, adding patient records, viewing records, searching patient information, updating appointment status, deleting records, clearing input fields, and safely exiting the system. It also applies input validation to prevent common errors, such as blank fields, duplicate patient IDs, invalid names, incorrect age input, and contact numbers that do not contain exactly eleven digits. Patient data are stored in a MySQL database while a duplicate copy is automatically saved in an Excel file for backup and reporting purposes. The results of system testing showed that MediTrack successfully performed its intended functions and prevented invalid information from being saved. Overall, MediTrack provides a practical, user-friendly, and efficient solution for improving clinic appointment scheduling and patient record management.